An inhalational swine model for the characterization of physiological effects and toxicological profile associated with cyanide poisoning. (6th December 2018) - Rivera-Burgos, Dinelia; Babin, Michael C.; Staugler, Jillian M.; Vinci, Thomas; Perry, Mark R.
Abstract: Cyanides are highly toxic compounds that have been used as weapons of terrorism throughout history. Cyanide (CN) is acutely toxic by all routes of administration; however, inhalation is the main exposure route. To adequately test effective countermeasures against inhalational CN threats, robust and well-characterized animal models are needed. This paper describes the initial development of a hydrogen cyanide (HCN) exposure swine model for documenting the physiological effects and toxicological profile during and after HCN inhalation exposure. Animals were implanted with telemetry transmitters for heart rate (HR), blood pressure, and electrocardiogram monitoring, and vascular access ports for serial blood collections. Nine female swine were exposed to HCN concentrations of 500 ± 6 ppm while breathing parameters were monitored real-time. Inhaled HCN doses ranged from 2.02 to 2.83 mg/kg. Clinical signs included vocalization, agitation, salivation, respiratory distress and apnea. After HCN exposure initiation, systemic arterial pressure fell dramatically with a concomitant increase in HR. Blood samples were collected to determine CN blood levels using LC-MS/MS and blood gas analysis. In summary, the developed HCN inhalation swine model permitted documentation of the physiological effects associated with CN poisoning. This model could be used to evaluate potential CN medical countermeasures in the event of a public health emergency stemming from inhalational CN threats.